Rancang Bangun Aplikasi Adminitrasi Pernikahan Pada Kantor Urusan Agama Kecamatan Sungai Rotan Berbasis Web - Resti Dewi Yanti; Muchlis Muchlis; Hepny Samosir (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
In the current digital era, the use of information technology has become an important need in various fields, including in wedding administration. The web-based wedding administration application at the Sungai Rotan District Religious Affairs Office is a web-based application design aimed at optimizing and simplifying the marriage administration process at the Religious Affairs Office in the Sungai Rotan District area. Weddings are an important moment in people's lives, and to ensure a smooth administrative process, this application aims to provide modern and efficient technological solutions. Thus, it is hoped that this application can provide better services to prospective brides and grooms and increase public satisfaction in arranging their weddings through the Office of Religious Affairs.